2021
DOI: 10.3390/biom11081226
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Risk of Malignant Brain Tumors in Patients with Type 2 Diabetes Mellitus

Abstract: The risk of malignant brain tumors associated with metformin use has rarely been investigated in humans. This retrospective cohort study investigated such an association. Patients with new-onset type 2 diabetes mellitus diagnosed from 1999 to 2005 in the nationwide database of Taiwan’s national health insurance were used to enroll study subjects. We first identified an unmatched cohort of 153,429 ever users and 16,222 never users of metformin. A cohort of 16,222 ever users and 16,222 never users matched on pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
(119 reference statements)
0
8
0
Order By: Relevance
“…There are some clinical implications in the present study. First, together with the finding of a protective effect of metformin on malignant brain tumors seen in our previous study [11], metformin might also provide a protective effect on the development of BBT, in terms of cerebral meningioma and/or other types of BBT (Tables 2 and 3). These observations suggested that there might be some common pathophysiological pathways involved in the development of either malignant or benign brain tumors.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…There are some clinical implications in the present study. First, together with the finding of a protective effect of metformin on malignant brain tumors seen in our previous study [11], metformin might also provide a protective effect on the development of BBT, in terms of cerebral meningioma and/or other types of BBT (Tables 2 and 3). These observations suggested that there might be some common pathophysiological pathways involved in the development of either malignant or benign brain tumors.…”
Section: Discussionmentioning
confidence: 59%
“…Major comorbidities included hypertension, dyslipidemia, obesity, chronic obstructive pulmonary disease, tobacco abuse, alcohol-related diagnoses and ocular pterygium (used as a surrogate of UV sunlight exposure). The ICD-9-CM codes for the above diagnoses have been described previously [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiological studies, meta-analyses and animal studies have revealed that MET has anti-neoplastic and chemopreventive activities ( 20 , 81 ) despite mixed results observed in other studies ( 82 , 83 ). Indeed, diabetic patients taking MET have significantly reduced risk of cancer and lower cancer-related mortality ( 84 89 ). Several small-scale clinical trials have shown the ability of MET to induce favorable cellular and molecular changes in cancer patients ( 90 93 ).…”
Section: Metformin Has Antitumor Properties That May Synergize With the Antitumor Activity Of Doxmentioning
confidence: 99%
“…In addition, the diabetes is a disease with which clinical aspects are related to cardiovascular and cerebral accidents [9], [10], and today it is associated with mortality generated by COVID-19 [11], [12]. Therefore, it is important to prevent, diagnose and treat diabetes [13], [14].…”
Section: Blood Testsmentioning
confidence: 99%